New Conjugate Gradient Method for Unconstrained Optimization with Logistic Mapping - Shareef, Shareef G.; Khatab, Hussein A.; Ismael, Sawsan S. (Science Journal of University of Zakho, 2016)
In this paper , we suggested a new conjugate gradient algorithm for unconstrained optimization based on logistic mapping, descent condition and sufficient descent condition for our method are provided. Numerical results show that our presented algorithm is more efficient for solving nonlinear unconstrained optimization problems comparing with (DY) .